2006
DOI: 10.1152/jn.01072.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Task Difficulty and Target Likelihood in Area V4 of Macaque Monkeys

Abstract: sell. Effects of task difficulty and target likelihood in area V4 of macaque monkeys. J Neurophysiol 96: 2377-2387, 2006. First published July 19, 2006 doi:10.1152/jn.01072.2005. Spatial attention improves performance at attended locations and correspondingly modulates firing rates of cortical neurons. The size of these behavioral and neuronal effects depends on the difficulty of the task performed at the attended location. Psychological theorists have attributed this to a tighter focus of a fixed amount of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 37 publications
8
79
0
Order By: Relevance
“…Third, most of the fMRI studies have cycled between attended locations every 20 -40 s, which is not considerably different from the amount of time spent within a trial block in our design. Finally, although it is true that neuronal responses may not be modulated by attention if subjects are presented with a task that is not challenging (Boudreau et al, 2006), we do not think that our task was too easy, because it required nearthreshold discriminations, behavioral measures showed that attention was critical for achieving good performance (Fig. 1b), and the task performance in our study was similar to that reported in fMRI studies.…”
Section: Discussionsupporting
confidence: 79%
“…Third, most of the fMRI studies have cycled between attended locations every 20 -40 s, which is not considerably different from the amount of time spent within a trial block in our design. Finally, although it is true that neuronal responses may not be modulated by attention if subjects are presented with a task that is not challenging (Boudreau et al, 2006), we do not think that our task was too easy, because it required nearthreshold discriminations, behavioral measures showed that attention was critical for achieving good performance (Fig. 1b), and the task performance in our study was similar to that reported in fMRI studies.…”
Section: Discussionsupporting
confidence: 79%
“…One theoretically possible explanation for our pattern of results is that the animals had different levels of arousal/attentional effort during Tracking relative to Attend-Fixation trials (i.e., performance during Attend-Fixation was significantly higher than during Tracking) (Spitzer et al, 1988;Boudreau et al, 2006;Chen et al, 2008). In our experiments, at least three factors argue against this explanation.…”
Section: Discussionmentioning
confidence: 69%
“…If the monkeys' attentional state was under stronger control by using a more difficult task (23,24) or if the task the monkey engaged in more closely matched the information that was to be decoded (e.g., if the monkey was doing a shape discrimination task rather than a color change detection task), the effects of attention might have been even stronger. Additionally, we have seen in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%